Role of Handedness in Conducting an Ultrasound-Guided Procedure: A Comparative Study. (September 2022) - Yoosaf, Shifa Shajahan; Umer Mohamed, Zubair; Sugashini, Veerasamy; Ravindran, Greeshma C.; Kumar, Lakshmi
Objective: Sonography is widely used by clinicians to provide imaging assistance in guiding invasive procedures. Many sonography users tend to prefer their dominant hand to operate the needle and their nondominant hand on the ultrasound transducer. The aim was this study was to determine whether the dominant hand guiding the needle achieves a faster time to target during ultrasound-guided procedures compared with the nondominant hand. Materials and Methods: Forty novice sonography users, medical students, were randomized to participate in the study. Twenty medical students used a Sonosite® ultrasound equipment system and the other 20 used a Mindray® ultrasound equipment system. Following a video education training session, an informed consent was obtained from each participant. In each equipment group, participants were randomly allocated to either a right-handed needle and a left-handed transducer preference or a left-handed needle and right-handed transducer preference group. A total of ten participants were in each group. A timer was started when the ultrasound transducer came in contact with the phantom model and stopped when the needle reached the target. This simulated task was repeated ten times by the participants. The hand arrangement for the needle and transducer was then switched and the task repeated another ten times by each participant. Results: Handedness was observed over multiple attempts and "time to target" was recorded for groups with both hand preferences and varied ultrasound equipment systems. The most significant finding was that the difference in time was statistically significant between the groups, when comparing the first and fifth procedural attempts. Conclusion: In this novice group of users, despite training for ultrasound-guided procedures using phantom models, irrespective of the ultrasound equipment system, or hand preference, there was no difference in the time to target.